Pelayanan Air Bersih oleh Badan Pengelolaan Air Bersih Nagari (BPABN) di Nagari Lansek Kadok Kabupaten Pasaman - Hose Pranando, Yuda; Fitri, Annisa (Dinasti Review Publisher, 2023)
This research is motivated by the lack of optimal implementation of public services, especially clean water services carried out by the Nagari Lansek Kadok Clean Water Management Agency (BPABN) in Nagari Lansek Kadok, Pasaman Regency because there are still customers who complain about the services provided by BPABN. This type of research is qualitative with descriptive methods. The selection of informants was carried out using a purposive sampling technique. The types of data are primary data and secondary data collected through observation, interviews, and documentation studies. Meanwhile, data validity testing was carried out using source triangulation techniques. Then the data is analyzed by means of data reduction, data analysis, and drawing conclusions or verification. Based on the research results, shows that the implementation of public services provided by the Nagari Lansek Kadok Clean Water Management Agency in Nagari Lansek Kadok, Pasaman Regency is still not optimal, because there are still customers who complain about the management's slowness in responding to customer complaints. The quality and quantity of BPABN managers in implementing public services are inadequate, as well as inadequate physical service facilities owned by BPABN.